Inhibition of growth and contraction in human prostate stromal cells by silencing of NUAK1 and -2, and by the presumed NUAK inhibitors HTH01-015 and WZ4003 - Liu, Yuhan; Wang, Ruixiao; Huang, Ru; Rutz, Beata; Ciotkowska, Anna; Tamalunas, Alexander; Hu, Sheng; Trieb, Moritz; Waidelich, Raphaela; Strittmatter, Frank; Stief, Christian G.; Hennenberg, Martin (Frontiers in Pharmacology, 2023)
Background: NUAKs promote myosin light chain phosphorlyation, actin organization, proliferation and suppression of cell death in non-muscle cells, which are critical for smooth muscle contraction and growth. In benign prostatic hyperplasia (BPH), contraction and growth in the prostate drive urethral obstruction and voiding symptoms. However, a role of NUAKs in smooth muscle contraction or prostate functions are unknown. Here, we examined effects of NUAK silencing and the presumed NUAK inhibitors, HTH01-015 and WZ4003 on contraction and growth-related functions in prostate stromal cells (WPMY-1) and in human prostate tissues. Methods: Effects of NUAK1 and -2 silencing, HTH01-015 and WZ4003 on matrix plug contraction, proliferation (EdU assay, Ki-67 mRNA), apoptosis and cell death (flowcytometry), viability (CCK-8) and actin organization (phalloidin staining) were examined in cultured WPMY-1 cells. Effects of HTH01-015 and WZ4003 on smooth muscle contraction were assessed in organ bath experirments with human prostate tissues. Results: Effects of silencing were most pronounced on proliferation and cell death, resulting in decreases of proliferation rate by 60% and 70% by silencing of NUAK1 and NUAK2 (compared to scramble siRNA-transfected controls), decreases in Ki-67 by 75% and 77%, while numbers of dead cells after silencing of NUAK1 and NUAK2 amounted to 2.8 and 4.9 fold of scramble-transfected controls. Silencing of each isoform was paralleled by reduced viability, breakdown in actin polymerization, and partial decreases in contractility (maximally 45% by NUAK1 silencing, 58% by NUAK2 silencing). Effects of silencing were mimicked by HTH01-015 and WZ4003, with numbers of dead cells amounting up to 16.1 fold or 7.8 fold with HTH01-015 or WZ4003, compared to solvent-treated controls. Using concentrations of 500 nM, neurogenic contractions of prostate tissues were inhibited partly by HTH01-015 and U46619-induced contractions were inhibited partly by HTH01-015 and WZ4003, while α1-adrenergic and endothelin-1-induced contractions remained unaffected. Using 10 µM, inhibition of endothelin-1-induced contractions by both inhibitors and inhibition of α1-adrenergic contractions by HTH01-015 added to effects seen by 500 nM. Conclusions: NUAK1 and -2 suppress cell death and promote proliferation in prostate stromal cells. A role in stromal hyperplasia appears possible in BPH. Effects of NUAK silencing are mimicked by HTH01-015 and WZ4003.